Intraocular pressure control after Nd:YAG laser posterior capsulotomy in eyes with glaucoma. Issue 3 (22nd January 2008) - Lin, J-C; Katz, L J; Spaeth, G L; Klancnik, J M
Abstract : Background and objectives: To evaluate the long-term intraocular pressure (IOP) control of glaucomatous eyes following Nd:YAG laser capsulotomy. Materials and methods: We performed a retrospective study of 69 glaucoma patients who underwent an Nd:YAG laser posterior capsulotomy over a 3 year period, following cataract extraction or a combined cataract–glaucoma procedure. All patients had a minimum follow-up period of at least 6 months and a median follow-up period of 2 years. We assessed IOP control, number of glaucoma medications required and whether the patient needed additional glaucoma surgery following the capsulotomy. Based on these outcome measures, we strictly defined "disease progression" as one of the following: an IOP rise of at least 5 mm Hg on two consecutive visits, addition of one or more glaucoma medications and additional glaucoma surgery following the capsulotomy. We calculated Kaplan–Meier event rate curves for these eyes with "disease progression". Results: The rate of "disease progression" was 11.6% at 4 months, 20.3% at 6 months, 38.1% at 12 months, 46.1% at 24 months, 52.1% at 36 months and 52.1% at 47 months following the capsulotomy. Conclusion: Gradual IOP elevation or a need for more aggressive therapy is common in glaucoma patients following Nd:YAG laser posterior capsulotomy. It is unclear whether this progression is related directly to the Nd:YAG laser procedure or whether it is an independent progression of the patient's glaucoma unrelated to the Nd:YAG laser procedure.